Design Improvement of a BWB Aerodynamic Performance at Cruise and Take-Off Speeds. (23rd November 2022) - Yu, Gang; Duan, Yuling
Abstract : As a high-performance aircraft, BWB (blended wing body) has attracted the attention of many countries around the world. A 300-seat BWB design is proposed by the Airplane Concept Design Institute of Northwestern Polytechnical University, which is also called SWB. The aerodynamic performance of it is evaluated by CFD (computational fluid dynamics). The CFD calculation method is based on RANS (Reynolds-averaged Navier–Stokes), and it is verified by wind tunnel test results at take-off speed. However, the aerodynamic design of the SWB needs to be improved to meet the market demand to increase its cruise Mach number from 0.8 to 0.85. To achieve this goal, firstly, based on the previous calculation and analysis results, the basic shape of SWB is improved by using "aft-body extending" technology and discrete adjoint optimization method. Then, the winglets are applied to the improved basic shape to improve its cruise speed aerodynamic performance, and the Krueger flaps are applied as its high-lift device to improve its take-off and landing aerodynamic performance. The CFD calculation and wind tunnel test results show that these improvements make SWB-2 have a good aerodynamic performance at the Mach number of 0.85. Therefore, these design improvements are appropriate and effective for improving the aerodynamic performance of BWB.